PRESS RELEASE: SIGNIFICANT EXTEND OF POSSIBILITIES FOR REGIONAL CARDIOLOGISTS - THE MAIN TASK OF THE SECOND YEAR NATIONAL AWARD IN CARDIOLOGY "PURPLE HEART" (Столичная издательская компания, 2016)
Press release: significant extend of possibilities for regional cardiologists - the main task of the second year National award in cardiology "Purple heart".